Construction and Application of Virtual Experiment Teaching System for Integrated Mapping of Unmanned Ship. Issue 1 (May 2021) - He, Yuanrong; Sun, Ruping; Wang, Yuli; Nie, Dewei; Wang, Weisen
Abstract: At present, China's water pollution situation is still very serious, and water pollution prevention is an important part of ecological environment protection, and water quality monitoring and pollution traceability are the basis of prevention and control work. Unmanned ship system uses GNSS intelligent navigation and positioning technology, automatic obstacle avoidance technology, real-time communication technology, sonar sounding technology and manual control technology, etc., by collecting underwater terrain, water quality information and underground pipe detection, it can complete water quality detection unmanned, intelligent and efficient. In this paper, the system architecture and measurement principle of unmanned equipment are comprehensively expounded, and based on WebGL and virtual simulation technology, an open unmanned equipment virtual simulation training system is constructed, which can directly carry out assembly training of unmanned aircraft and unmanned ship and flight control training of unmanned aircraft on the Web side. Finally, the feasibility and development prospect of unmanned equipment in sewage monitoring are discussed with an application example.